2019
DOI: 10.1039/c8fo02416b
|View full text |Cite
|
Sign up to set email alerts
|

Simulated gastrointestinal digestion of inclusion complexes based on ovalbumin nanoparticles and conjugated linoleic acid

Abstract: Ovalbumin delivery system of conjugated linoleic acid resists in vitro gastrointestinal digestion with high percentages of bioactive retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…During in vitro static GI digestion, a significant amount of encapsulated chrysin is kept inside the particles, resulting in the release of 14% of this bioactive substance. To test the effect of chitin nanocrystals on the digestion of maize oil-in-water emulsions (stabilised with tween 80) and the consequent bioaccessibility of β-carotene encapsulated into this lipidic-based delivery system, a standardised in vitro digestion regimen was developed [87]. The results obtained demonstrated that micro chitin decreases the bioaccessibility of β-carotene via limiting lipid digestion.…”
Section: Static Modelsmentioning
confidence: 99%
“…During in vitro static GI digestion, a significant amount of encapsulated chrysin is kept inside the particles, resulting in the release of 14% of this bioactive substance. To test the effect of chitin nanocrystals on the digestion of maize oil-in-water emulsions (stabilised with tween 80) and the consequent bioaccessibility of β-carotene encapsulated into this lipidic-based delivery system, a standardised in vitro digestion regimen was developed [87]. The results obtained demonstrated that micro chitin decreases the bioaccessibility of β-carotene via limiting lipid digestion.…”
Section: Static Modelsmentioning
confidence: 99%
“…Rao et al fabricated ovalbumincarvacrol gel nanoparticles which show physicochemical and antibacterial properties [16]. Ovalbumin complex nanoparticles exhibit good encapsulation efficiency [17].…”
Section: Types Of Albuminmentioning
confidence: 99%